Endoscopy: Chromoendoscopy in IBD: indispensable in real-life screening - Atreya, Raja; Neurath, Markus (Nature Reviews Gastroenterology & Hepatology, 2016)
Long-standing IBD is associated with an increased risk of neoplasia. Chromoendoscopy was proven to be the most sensitive modality for dysplasia detection in several clinical trials, but a new study has now shown ityto be an effective screening strategy in a routine clinical setting, further warranting its implementation into real-world practice.
EVALuna2:2193